The Effectiveness of Coordinated Locomotor Movement Training to The Balance and Agility of Intellectual Impairment (Media Ilmu Keolahragaan Indonesia, 2022)
Abstract. Children with intellectual impairment have a lack of locomotor movement than non-intellectual impairment.  A motoric activity like walking and running of intellectual impairment showed decreased balance and agility. The study investigated the locomotor exercise effect on increasing balance and agility the children with intellectual impairment. Quasi-experiment with one group pre-test and post-test design was used in the study. Sampling technique using Purposive Sampling and Ten children with Intellectual Impairment at Roemah Disabled Semarang who have Movement Balance and Agility Barriers became the research sample. While the technique of data collection by observing the movement of balance and agility on the subject. They followed the intervention 16 times, each time for 40 minutes, each exercise  3-5 repetitions and 3-5 sets, and minutes for rest. The intervention exercise was locomotor coordination, like walking, running, and jumping. The balance and agility were tested before and after the intervention. The data were analyzed using the Wilcoxon test. The result of the study showed that static balance significantly increased from (50 ±17.91) to (90.10 ± 15.94), p = 0.007, after 16 times locomotor exercises. The agility improved significantly before (46.60 ± 17.55) and after  (86.80±17.04 ), p = 0.007 the intervention. The study concluded that locomotor coordination exercise intervention 16 times improved dynamic balance and agility of intellectual impairment.Abstract in Indonesia. Intellectual impairment memiliki keterbatasan gerak lokomotor dibandingkan anak non intelektual. Aktivitas motorik seperti berjalan dan berlari pada gangguan intelektual menunjukkan penurunan keseimbangan dan kelincahan. Tujuan Penelitian ini yaitu ingin mengetahui pengaruh latihan koordinasi gerak lokomotor terhadap peningkatan keseimbangan dan kelincahan intellectual impairment. Metode yang digunakan dalam penelitian yaitu Quasi-experiment dengan desain one group pre-test dan post-test. Teknik Sampling dengan menggunakan Purposive Sampling Serta Sepuluh anak intellectual impairment di Roemah Difabel Semarang yang memiliki Hambatan Gerak Keseimbangan dan Kelincahan menjadi sampel penelitian. Sedangkan teknik pengumpulan data dengan observasi pengamatan gerak keseimbangan dan kelincahan pada subyek. Mereka mengikuti perlakuan sebanyak 16 kali, setiap kali selama 40 menit, setiap latihan 3-5 repetisi dan 3-5 set. Latihan yang dilakukan adalah koordinasi lokomotor, seperti berjalan, berlari, dan melompat. Keseimbangan dan kelincahan diuji sebelum dan sesudah diberikan perlakuan. Data dianalisis menggunakan uji Wilcoxon. Hasil penelitian ini menunjukkan bahwa terjadi peningkatan pada 10 subyek setelah diberikan latihan gerak lokomotor. Rata rata perkembangan keseimbangan Pre-Test(50±17,91) Posttest (90,10± 15,94) p=0,007 dan kelincahan pada pretest(46,60 ±17,55) dan posttest sebesar (86,80±17.04), p=0,007, Berdasarkan tes statistik,Diketahui Asymp. Sig(2-talled) bernilai 0,007. Atau p0,05. Hasil penelitian menyimpulkan bahwa latihan koordinasi lokomotor 16 kali meningkatkan keseimbangan Dinamis dan kelincahan pada anak gangguan intelektual.